القضاء الاستعجالي في المنازعات الادارية على ضوء تعديل قانون الاجراءات المدنية والادارية لسنة 2022 - قويدري ،سفيان; قدوري، الساسي; قروي ،محمد السعيد (جامعة الوادي University of El Oued, 2024)
يعد الاستعجال في المادة الادارية من أهم المواضيع التي تشغل اهتمام المواطن والقضاء والادارة على حد سواء، ذلك أنه مرتبط أساسا بتدخل الادارة للقيام بمهامها خدمة للمصلحة العامة، الامر الذي يجعلها في كثير من الاحيان في مواجهة مع مصالح الأفراد، مما يستدعي وجود قضاء مستعجل لوقف التعدي ومنع الضرر الذي لا يمكن التراجع عنه، خاصة وأن الادارة هي الطرف القوي والتي تملك دائما من اجل القيام بمهامها السلطة العامة، ولما كان الامر على ما هو عليه فإن القضاء الاستعجالي الاداري يعيد التوازن، ويحقق لكل الاطراف مزيدا من السبل التي تكفل الاستمرارية بين تحقيق المصلحة العامة وحفظ المصلحة الفردية، ويأتي التعديل الأخير لقانون الاجراءات المدنية والادارية لتكريس مزيد من تحقيق العدالة من خلال التأسيس الفعلي لمبدأ التقاضي على درجتين في المادة الادارية من خلال إنشاء المحاكم الادارية للإستئناف، على غرار ماهو معمول به في القضاء العادي. Urgency in administrative matters is one of the most important topics that concern citizens, the judiciary, and the administration alike. This is because it is essentially linked to the administration's intervention to carry out its tasks in the service of the public interest, which often puts it in conflict with the interests of individuals. This necessitates the existence of urgent administrative judiciary to stop encroachment and prevent irreparable harm, especially since the administration is the strong party that always has the public authority to carry out its tasks. As such, administrative urgent judiciary restores balance and provides all parties with more ways to ensure continuity between achieving the public interest and preserving the individual interest. The recent amendment to the Civil and Administrative Procedures Code comes to consecrate the further realization of justice through the actual establishment of the principle of two-degree litigation in administrative matters by creating administrative courts of appeal, similar to what is practiced in the ordinary judiciary.
ماستر اداري